2016
DOI: 10.1007/s00167-016-4394-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered patterns of displacement within the Achilles tendon following surgical repair

Abstract: PurposeUltrasound speckle tracking was used to compare tendon deformation patterns between uninjured and surgically repaired Achilles tendons at 14–27-month follow-up. The hypothesis was that the non-homogenous displacement pattern previously described in uninjured tendons, where displacement within deep layers of the tendons exceeds that of superficial layers, is altered following tendon rupture and subsequent surgical repair.MethodsIn the first part of this study, an in-house-developed block-matching speckle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 34 publications
4
38
0
Order By: Relevance
“…The settings we chose were based on trial and error to find somewhat optimal settings for our heel‐rise recordings. Previous studies have reported similar results showing the speckle algorithm being a bit conservative . Others have performed a similar validation of the speckle tracking method in an in vitro animal model and reported a mean tracking error of 1.6%, which is close to the data of the present human in vivo study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The settings we chose were based on trial and error to find somewhat optimal settings for our heel‐rise recordings. Previous studies have reported similar results showing the speckle algorithm being a bit conservative . Others have performed a similar validation of the speckle tracking method in an in vitro animal model and reported a mean tracking error of 1.6%, which is close to the data of the present human in vivo study.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported similar results showing the speckle algorithm being a bit conservative. 12 Others 11 have performed a similar validation of the speckle tracking method in an in vitro animal model and reported a mean tracking error of 1.6%, which is close to the data of the present human in vivo study. A: Data are presented as the mean AE SD (pixel) displacement for the 4 rows tracked at 2 separate recordings of the same exercise.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To date, speckle-tracking studies have focused almost exclusively on large energy-storing tendons such as the Achilles (Arndt et al, 2012; Brown et al, 2013; Å. Fröberg et al, 2016; Nuri et al, 2016; Slane and Thelen, 2015, 2014b) and patellar (Lee et al, 2016; Pearson et al, 2014; Slane et al, 2017) tendons, with motivations often cited as their propensity for injury. However, there are also many practical advantages to studying these tendons, that thereby constitute complications when assessing the collateral ligaments.…”
Section: Challengesmentioning
confidence: 99%
“…This then requires smaller regions-of-interest (ROIs) for tracking, which can be prone to mismatch as well as lower repeatability and accuracy than larger ROIs (Fröberg et al, 2016). Further, the small varus/valgus range of motion means small frame-to-frame motion.…”
Section: Challengesmentioning
confidence: 99%